(untitled) (Chittagong University Journal of Biological Sciences, 2024)
The present study attempted an empirical investigation to explore the suicidal ideation and academic self-efficacy among urban high school students. A total of 120 (60 boys and 60 girls) respondents constituted the sample of the study. The samples were taken from 3 high schools of City Corporation, Chittagong district. The measuring instruments used in this study were: Adapted Bangla version of Suicidal Ideation of Beck et al. (1974), Adapted Bangla version of Academic self-efficacy scale of Owen md Froman ( 1988). The data were analyzed by using mean, standard deviation t-test and Pearson product moment correlation. The findings showed that there was no significant difference between boy and girl students with respect to suicidal ideation and academic self-efficacy. Results also showed that there was significant negative correlation of suicidal ideation and academic self-efficacy. The correlation coefficient between suicidal ideation and academic self-efficacy was r = - 0.215 (p< 0.05). The Chittagong Univ. J B. Sci. 8(1&2): 127-134, 2013